The Content of Our #Characters: Black Twitter as Counterpublic. Issue 4 (October 2016) - Graham, Roderick; Smith, 'Shawn
Much media attention has been placed on "Black Twitter, " a collective composed primarily of African Americans who have managed to effect change through the microblogging platform Twitter. Organized around the hashtag #BlackTwitter, this collection of users has been credited with injecting uniquely black concerns and perspectives into the national discourse. However, Black Twitter as an entity has not been theoretically contextualized and grounded in empirical research. In this research, the authors situate Black Twitter within the public sphere–counterpublic literature and ask the question: can Black Twitter be understood as a counterpublic? The authors compare Black Twitter, as indicated by the #BlackTwitter hashtag, with hashtags indicating the public sphere—#TCOT (Top Conservatives on Twitter) for conservatives and #UniteBlue for progressives—and with a hashtag indicating another potential counterpublic—#BCOT (Black Conservatives on Twitter). Using a corpus of 16, 000 tweets collected during a 10-day period, comparisons were made in interaction patterns (tweets, favorites, and replies) and thematic content. The findings suggest that compared with other hashtags and the publics they represent, #BlackTwitter possesses more of the characteristics of a counterpublic.